Sex differences in sand lizard telomere inheritance: paternal epigenetic effects increases telomere heritability and offspring survival - Olsson, M; Pauliny, A; Wapstra, E; Uller, T; Schwartz, T; Blomqvist, D (Public Library of Science, 2011)
BACKGROUND: To date, the only estimate of the heritability of telomere length in wild populations comes from humans. Thus, there is a need for analysis of natural populations with respect to how telomeres evolve. METHODOLOGY/PRINCIPAL FINDINGS: Here, we show that telomere length is heritable in free-ranging sand lizards, Lacerta agilis. More importantly, heritability estimates analysed within, and contrasted between, the sexes are markedly different; son-sire heritability is much higher relative to daughter-dam heritability. We assess the effect of paternal age on Telomere Length (TL) and show that in this species, paternal age at conception is the best predictor of TL in sons. Neither paternal age per se at blood sampling for telomere screening, nor corresponding age in sons impact TL in sons. Processes maintaining telomere length are also associated with negative fitness effects, most notably by increasing the risk of cancer and show variation across different categories of individuals (e.g. males vs. females). We therefore tested whether TL influences offspring survival in their first year of life. Indeed such effects were present and independent of sex-biased offspring mortality and offspring malformations. CONCLUSIONS/SIGNIFICANCE: TL show differences in sex-specific heritability with implications for differences between the sexes with respect to ongoing telomere selection. Paternal age influences the length of telomeres in sons and longer telomeres enhance offspring survival.